2014
DOI: 10.1136/gutjnl-2013-305863
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon signalling in the intestinal epithelium affects Paneth cells, microbial ecology and epithelial regeneration

Abstract: IFNAR1 in IECs, and Paneth cells in particular, contributes to the regulation of the host-microbiota relationship, with consequences for intestinal regeneration and colitis-associated tumour formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 62 publications
6
78
0
1
Order By: Relevance
“…In contrast, Enterobacteriaceae, another family of proinflammatory microbes found to have increased relative abundance in CD patients in both our cohort and the RISK study, did not correlate with Paneth cell phenotype, suggesting that the presence of inflammation may play a more important role than Paneth cell phenotype for Enterobacteriaceae colonization in CD. Together, our study and other previous reports suggest multiple mechanisms for how proinflammatory microbes become associated with CD patients (35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, Enterobacteriaceae, another family of proinflammatory microbes found to have increased relative abundance in CD patients in both our cohort and the RISK study, did not correlate with Paneth cell phenotype, suggesting that the presence of inflammation may play a more important role than Paneth cell phenotype for Enterobacteriaceae colonization in CD. Together, our study and other previous reports suggest multiple mechanisms for how proinflammatory microbes become associated with CD patients (35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 78%
“…Genetic studies using the Ifnar1 knockout in mice have yet to establish the role of IFN in regulating intestinal epithelial cell proliferation. Ablation of Ifnar1, specifically in IECs (Ifnar1 ⌬IEC ), resulted in only a modest increase in bromodeoxyuridine (BrdU) labeling, and this increase was dependent on the changes in the commensal microbiota (16). However, neither alteration in the microbiome profile (17) nor increased IEC proliferation (17,18) was observed in mice lacking Ifnar1 in all tissues compared to wild-type mice.…”
mentioning
confidence: 92%
“…We and others have found that molecular changes in processes such as autophagy and TNF signaling converge to affect Paneth cell function in CD patients and mouse models of intestinal inflammation (19,45,52,69,70). This in turn correlates with the development of dysbiosis and inflammation (20).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%